Update on cardiomyopathies and sudden cardiac death - Stefania Rizzo; Elisa Carturan; Monica De Gaspari; Kalliopi Pilichou; Gaetano Thiene; Cristina Basso (Oxford University Press, 2019)
Sudden cardiac death (SCD) remains a leading mode of death in western countries. Since SCD can be the first and last clinical presentation of the underlying disease, autopsy could be the only medical examination available for early diagnosis and it should be performed according to the guidelines of the Association for European Cardiovascular Pathology. Although the vast majority of SCD are due to coronary artery disease, non-ischemic causes of SCD do exist and are prevalent in young people with structural (i.e. arrhythmogenic, hypertrophic and inflammatory cardiomyopathy) and non-structural (ion channel diseases) cardiomyopathies, accounting for up to one half of cases. A standardized autopsy protocol, in combination with blood sampling to ensure feasibility of postmortem molecular testing if needed, is mandatory. The pathologist is called to provide the correct diagnosis and to advice the relatives on the need of a cascade clinical and genetic screening in the presence of a heredo-familial disease.